Molecular evidence for the role of inflammation in dry eye disease. (10th January 2019) - Ganesalingam, Kalaivarny; Ismail, Salim; Sherwin, Trevor; Craig, Jennifer P
Abstract : Ocular surface inflammation is propagated by a complex series of molecular processes and has been implicated in the pathogenesis of dry eye disease (DED), either as a causal or a downstream effect of ocular surface disease. A state of hyperosmolarity elicits an acute immune response in DED, leading to subsequent activation of the adaptive immune response. This cascade incites dysregulation of the immune system, triggering a vicious cycle of events that causes damage to the ocular surface. Symptoms associated with these events include burning, irritation, redness, photophobia and blurred vision. The chronic nature of the disease process can cause permanent alterations to the ocular surface and adnexa. An increasing investment in treatment options, and positive outcomes with novel therapies that have received subsequent regulatory approval, lends further support to the role of inflammation in DED. This review highlights the nature and function of a range of fundamental inflammatory molecules in DED to provide the clinician with an appreciation for the ways in which these factors might be manipulated in DED management.